Change of the rainfall seasonality over central peruvian andes: Onset, end, duration and its relationship with large-scale atmospheric circulation - Giráldez L. (2020)
Changes of the onset dates, end dates, and duration of the rainy season over central Peruvian Andes (Mantaro river basin, MRB) could severely affect water resources management and the main economic activities (e.g., rainfed agriculture, raising cattle, among others). Nonetheless, these changes have not been documented for the Tropical Andes. To asses that, we used daily datasets of observed rainfall during the 1965-2013 period. For this period, the average onset (end) date of the rainy season over the MRB occurs in the pentad 17 (19-23 September) [pentad 57 (7-11 April)]. The duration of the rainy season mainly is modulated by the onset dates due to it has higher variability than end dates. There is a reduction of 3 days/decade in the duration of wet season over the MRB for the last four decades due to the delay of the onset days. Furthermore, El Nino favors late-onset and early end of the rainy season, while La Nina favors early onset and late end of the rainy season in the MRB. Onset dates are related to the propagation of the convective region of the South American Monsoon System (SAMS), from the Caribbean region toward the central Amazon basin. Early (late)-onset days are associated with a southward (northward) shift of the South Atlantic Convergence Zone (SACZ) and weak (strong) convection over equatorial Atlantic that induces the southernmost propagation (eastward shift) of the SAMS. © 2020 by the authors.